2017
DOI: 10.1183/16000617.0079-2017
|View full text |Cite
|
Sign up to set email alerts
|

Lung segmentectomy: does it offer a real functional benefit over lobectomy?

Abstract: @ERSpublicationsLung segmentectomy offers mild post-operative to small long-term functional benefits over lobectomy http://ow.ly/dcPQ30fuCU9Cite this article as: Charloux A, Quoix E. Lung segmentectomy: does it offer a real functional benefit over lobectomy ? Eur Respir Rev 2017; 26: 170079 [https://doi.org/10.1183/16000617.0079-2017.ABSTRACT Anatomical segmentectomy has been developed to offer better pulmonary function preservation than lobectomy, in stage IA lung cancer. Despite the retrospective nature of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
51
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(59 citation statements)
references
References 61 publications
2
51
0
6
Order By: Relevance
“…We do not routinely have patients undergoing pulmonary function test after operation; actual difference in recovery of pulmonary function between different extents of pulmonary resections was unknown in our series. It is believed that segmentectomy provided mild postoperative and small long-term benefits over lobectomy in pulmonary function (24). Although we demonstrated that uniportal surgical lung resection is a feasible method for the treatment of lung sequestration, we considered a relatively small number of cases.…”
Section: Discussionmentioning
confidence: 95%
“…We do not routinely have patients undergoing pulmonary function test after operation; actual difference in recovery of pulmonary function between different extents of pulmonary resections was unknown in our series. It is believed that segmentectomy provided mild postoperative and small long-term benefits over lobectomy in pulmonary function (24). Although we demonstrated that uniportal surgical lung resection is a feasible method for the treatment of lung sequestration, we considered a relatively small number of cases.…”
Section: Discussionmentioning
confidence: 95%
“…It is widely believed that pulmonary function can be preserved to a greater degree by combining sublobar resection with less invasive thoracoscopic surgery. 22 Reports with encouraging outcomes from sublobar resection for the treatment of small-sized, noninvasive or minimally invasive lung cancer have been increasing. 3,4,6,[23][24][25] Although wedge resection is also increasingly considered to be sufficiently effective in patients with radiologically noninvasive tumors, [26][27][28] we considered segmentectomy as the preferred option before the final results of the randomized clinical studies published.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies show that segmentectomy preserves more lung tissue and therefore promotes lung function recovery [33,37,38], but some reports suggest that the retained lung tissue provides little functional advantage [10,39]. There could be several explanations.…”
Section: Discussionmentioning
confidence: 99%